Navigating challenges and enriching perspectives: Insights into the experiences and success of international students - Gultekin, Osman (Journal of International Students, 2024)
This edition of the Journal of International Students presents ten papers from scholars across 12 countries, examining major themes the challenges of virtual learning and acculturation, barriers to equitable labor market access, and the impact of pandemic-related stress on international students. Through these studies, contributors provide actionable insights to enhance support for international student well-being, adaptation, and career readiness. This volume offers diverse, evidence-based insights to inform policies and practices that support the well-being and success of international students globally.